KEMAMPUAN MEMPRODUKSI TEKS EKSPLANASI MELALUI METODE SAINTIFIK PADA SISWA KELAS VIII SMPN 7MATARAM - Suherni, (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to evaluate the ability of class VIII students. A class majoring in Automotive at SMPN 7 Mataramuses the scientific method to make explanatory texts, which can be seen from the order of the intellectual structure of the text and the language resources used and related to how the teacher applies the text. scientific method for making explanatory text in teaching materials. This study uses a qualitative-quantitative approach because the information in the form of explanatory text and audio results of the application of the scientific method by teachers in the classroom in the form of numbers must be re-analyzed to validate the research. . Results The sample used consisted of 10 class VIII car majors at SMPN 7 Mataram which were taken randomly from each class. Sampling is based on the assumption that all class VIII students have the same characteristics of text production ability. Data collection is done through the method of observation and verification. Interlingual and extralingual methods of comparison of HBS, HBB and HBSP were used as data analysis methods. The results of this study are (a) teachers cannot use the scientific method to make explanatory texts that are displayed in teaching materials. If the publication score is 2, (b) a class VIII student. The automotive class at SMPN 7 Mataram was less able to make explanatory texts based on text structure, as evidenced by obtaining sample points for research. each class, namely 20, 16.66, 15.53 and 20, (c) Students of VIII grade at SMPN 7 Mataram were unable to use language tools in the explanation text produced with a score of 21, and (d) the ability of VIII gade students at SMPN 7 Mataram to write explanatory texts using the scientific method is still low reach only 39 degrees.